Thermomechanical performance and shape recovery behaviour of shape memory polymer nanocomposite incorporated with hexagonal boron nitride. Issue 1 (3rd January 2017) - Li, Zhenghong; Lu, Haibao; Yao, Yongtao; Lin, Long
Abstract : Purpose: The purpose of this paper is to develop an effective approach to significantly improve the thermomechanical properties of shape memory polymer (SMP) nanocomposites that show fast thermally responsive shape recovery. Design/methodology/approach: Hexagonal boron nitrides (h-BNs) were incorporated into polymer matrix in an attempt to improve the thermal conductivity and thermally responsive shape recovery behaviour of SMP, respectively. Thermally actuated shape recovery behaviour was recorded and monitored instrumentally. Findings: The results show that both glass transition temperature ( T g ) and thermomechanical properties of the SMP nanocomposites have been progressively improved with increasing concentration of h-BNs. Analytical results also suggest that the fast-responsive recovery behaviour of the SMP nanocomposite incorporated with h-BNs was due to the increased thermal conductivity. Research limitations/implications: A simple way for fabricating SMP nanocomposites with enhanced thermally responsive shape recovery based on the incorporation of h-BNs was developed. Originality/value: The outcome of this study may help fabrication of SMP nanocomposites with fast responsive recovery behaviour.